Exploring the integration of OFST and IPE in cross-regional physiology teaching-a novel approach - Ting-Huai Wang; Xiao-Dan Xu; Zhi-Yuan Long; Ying-Nan Cao; Ning-Yi Lai; Yong-Hong Ma; Xiao-Qiu Tan; Min Xin; Jin-Yan Jiang; Da-Ya Yang (BMC Medical Education)
Abstract Background Addressing regional disparities in educational resources remains a persistent challenge in medical education. The Online Four-Step Teaching (OFST) method is a structured, team-based, task-driven approach designed to enhance student engagement and learning outcomes sequentially. When combined with Interprofessional Education (IPE), which promotes cross-disciplinary collaboration among healthcare students, OFST has the potential to bridge geographical and disciplinary boundaries. This study evaluates the integration of OFST and IPE in cross-regional physiology instruction and its effectiveness in improving learning outcomes and fostering interprofessional collaboration. Methods 185 undergraduate students from ten majors across four eastern and western Chinese universities participated in an interprofessional OFST. The OFST includes four structured steps: Teacher Guidance, Self-Regulated Learning, Team Learning and Practice, and Experience Sharing. Through online platforms, students from diverse disciplines, including medicine, nursing, pharmacy, and medical imaging, etc. worked collaboratively in interprofessional teams. Guided learning, individual study, and collaborative problem-solving activities were combined with reflective discussions to consolidate knowledge. The international OFST’s effectiveness was assessed using individual quizzes and a survey evaluating learning outcomes, self-regulated learning, teamwork, and interprofessional collaborative learning. Results Correct rates for fundamental and practical application questions increased significantly from 48.3% (72/149) in Quiz 1 to 80.5% (120/149) in Quiz 2 (P < 0.001) and 22.8% (34/149) in Quiz 1 to 55.7% (83/149) in Quiz 2 (P < 0.001), respectively. Survey results showed that 82.4–94.1% of students believed OFST helped clarify their learning direction, enhance self-regulated learning and teamwork skills, and broaden disciplinary and interprofessional knowledge. Conclusions Integrating OFST with IPE enhances cross-regional and interprofessional collaboration, improves knowledge acquisition and fosters skills such as teamwork and self-regulated learning. This approach holds significant potential for addressing disparities in educational resources and advancing equity in medical education.